Evolution of innate-like T cells and their selection by MHC class I-like molecules - Edholm, Eva-Stina (Immunogenetics, 2016)
Until recently, major histocompatibility complex (MHC) class I-like-restricted innate-like αβT (iT) cells expressing an invariant or semi-invariant T cell receptor (TCR) repertoire were thought to be a recent evolutionary acquisition restricted to mammals. However, molecular and functional studies in Xenopus laevis have demonstrated that iT cells, defined as MHC class I-like-restricted innate-like αβT cells with a semi-invariant TCR, are evolutionarily conserved and prominent from early development in amphibians. As these iT cells lack the specificity conferred by conventional αβ TCRs, it is generally considered that they are specialized to recognize conserved antigens equivalent to pathogen-associated molecular patterns. Thus, one advantage offered by the MHC class I-like iTcell-based recognition system is that it can be adapted to a common pathogen and function on the basis of a relatively small number of T cells. Although iT cells have only been functionally described in mammals and amphibians, the identification of non-classical MHC/MHC class I-like genes in other groups of endothermic and ectothermic vertebrates suggests that iT cells have a broader phylogenetic distribution than previously envisioned. In this review, we discuss the possible role of iT cells during the emergence of the jawed vertebrate adaptive immune system.